Charismatic leadership among nursing professionals: an integrative review - André Almeida de Moura; Karen Yukari Hayashida; Andrea Bernardes; Ariane Cristina Barboza Zanetti; Carmen Silvia Gabriel
ABSTRACT Objective: Analyze the literature for knowledge about charismatic leadership among nursing professionals. Method: This is an integrative review of the literature that searched for studies published in English, Portuguese and Spanish until 2016 in the following electronic databases: LILACS, Pubmed, SCOPUS, Web of Science, and CINAHL. Results: Three studies were selected from a total of twenty-one studies; they were arranged in two categories: validation of a charismatic leadership instrument and effects of charismatic leadership on followers' initiative-oriented behavior. Conclusion: Charismatic leadership is considered an important skill for nursing professionals as they generate a positive influence on followers, especially in times of crisis and changes. Considering the relevance of this style of leadership, the need to develop further studies on this subject is reinforced, given the low number of studies found in the literature.